A Study of the Epidemiology, Clinical, and Phenotypic Characteristics of Inflammatory Bowel Disease in the Northen-Central Region of Saudi Arabia - Ahmed A. Al-Fawzan; Sulaiman A. Al-Radhi; Ahmed S. Al-Omar; Nawaf H. Al-Mutiri; Ammar M. Al-Ammari; Mohammad El-Gohary; Amal N. Shamsan; Hamdan M. Al Shehri; Naif S. ALGhasab (Diagnostics, 2023)
Background: Inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), is becoming increasingly prevalent in Saudi Arabia. However, there is limited data on the characteristics and manifestations of IBD in this population. This study aimed to establish a multi-center database of patients with IBD in the Qassim region of Saudi Arabia to better understand the demographics, prevalence, and manifestations of IBD in this population. Methods: This retrospective study included patients diagnosed with IBD at three healthcare facilities in the Qassim region of Saudi Arabia. The patient’s demographic and clinical characteristics, disease location and behavior, age at diagnosis, medication use, related surgeries, and extraintestinal manifestations were recorded based on the Montreal classification. A total of 257 patients with IBD were included in the study, of which 126 had UC and 131 had CD. Results: Of the 257 patients with IBD, 134 (52.2%) were male and 123 (47.8%) were female. The mean age of patients with CD and UC were 28.74 (range 15–67) and 38.79 (range 15–75) years, respectively. There was a significant difference between all age groups (p < 0.005), with more patients aged over 40 years being diagnosed with UC. UC was most commonly classified as left-sided UC (E2) (60; 47.6%), while the most common location of CD was the ileocolon (L3) (76; 58%). Non-stricturing and non-penetrating CD was the most common behavior (B1) (70; 53.8%). Approximately one-third of the patients with Crohn’s disease developed perianal disease (70; 27.2%), with fistulizing Crohn’s being the most prevalent manifestation (40; 30.5%), followed by abscess formation (10; 7.6%) and fissures (9; 6.8%). The most common extraintestinal manifestation was arthropathy (15; 5.8%). Significant p-values were detected for UC and CD (p = 0.036). Conclusions: This study provides crucial insights into the demographics, patterns, and manifestations of IBD in Saudi Arabia. The findings highlight the need for improved diagnosis, management, and treatment strategies for IBD in this population. The establishment of a multi-center database will help to facilitate future research and improve patient care in Saudi Arabia.